“MODEL PENGELOLAAN AIR BERSIH BERBASIS MASYARAKAT YANG BERWAWASAN LINGKUNGAN DI KOTA MAKASSAR” “CLEAN WATER MANAGEMENT MODEL BASED ON COMMUNITY-BASED ENVIRONMENT” - Sadewa, Arie Satriadi; Agustang, Andi; Pertiwi, Nurlita (Jurnal Ilmiah Mandala Education (JIME), 2022)
One of the basic needs of the community is the availability of clean water in their environment. The water that humans need is clean water, which according to the Regulation of the Minister of Health of the Republic of Indonesia No. 416/MENKES/PER/IX/1990 Requirements for Clean Water Quality, water that meets the requirements of clean, clear, odorless, colorless, does not contain germs and substances dangerous. At the request or offer from the Bulurokeng sub-district community through the Makassar City Government Public Works Service, in 2013 the Government provided the provision of clean water facilities for the Bulurokeng sub-district, known as the SPAM program. Drinking Water Supply System (SPAM). Based on data from the Makassar City Public Works Agency in 2021, the Drinking Water Supply System (SPAM) built in the Bulurokeng sub-district has several causes that cause the facilities built to malfunction. Therefore, the authors found a solution to re-operate clean water facilities by increasing the performance of managers through improving the management system. This study uses quantitative, descriptive, evaluative, and experimental methods to determine the effectiveness of community-based clean water management. The results of further research are based on the output of data processing based on the SMARTPLS software application to obtain recommendations or solutions for using the right model in improving community-based clean water management systems.